Improving the competence and confidence of pulmonary and critical care medicine fellows in performing a cricothyrotomy (Canadian Medical Education Journal, 2019)
Clinical opportunities to practice or perform a cricothyrotomy are limited. We developed an evidence-based cricothyrotomy course following the 4-phase lesson plan for simulation that provides pulmonary and critical care medicine fellows with demonstrations, practice, and feedback to increase their confidence and competence.Survey results demonstrated an improvement in perceived confidence (p